2013
DOI: 10.1515/hmbci-2013-0049
|View full text |Cite
|
Sign up to set email alerts
|

Per3 length polymorphism in patients with type 2 diabetes mellitus

Abstract: Background: A number of observations support the involvement of circadian clock genes in the regulation of metabolic processes. One of these circadian genes, Per3, exhibits a variable number tandem repeat length polymorphism, consisting of two alleles, namely four and five repeat alleles, in its exon 18. The objective of this study was to examine the existence of Per3 variants in patients with type 2 diabetes mellitus (T2DM) as compared to a non T2DM control group. Methods: Intravenous blood samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…These effects appear to be independent of sleep loss or diminished sleep quality, suggesting that disruption of the timing system alone can lead to metabolic dysfunction [19,20]. In support of this notion, the probability of a genetic polymorphism in the PER3 genetic locus was greater among individuals with type 2 diabetes, suggesting that altered activity of the PER3 protein, and thus the molecular clock, may be an independent risk factor for metabolic disease [93]. Finally, data show that the amount of social jet lag (a delay in mid-sleep time on 'off days' relative to work days) experienced is positively correlated with elevated BMI, independent of nightly sleep duration [94].…”
Section: Sleep Disturbance Circadian Disruption and Altered Glucose mentioning
confidence: 86%
“…These effects appear to be independent of sleep loss or diminished sleep quality, suggesting that disruption of the timing system alone can lead to metabolic dysfunction [19,20]. In support of this notion, the probability of a genetic polymorphism in the PER3 genetic locus was greater among individuals with type 2 diabetes, suggesting that altered activity of the PER3 protein, and thus the molecular clock, may be an independent risk factor for metabolic disease [93]. Finally, data show that the amount of social jet lag (a delay in mid-sleep time on 'off days' relative to work days) experienced is positively correlated with elevated BMI, independent of nightly sleep duration [94].…”
Section: Sleep Disturbance Circadian Disruption and Altered Glucose mentioning
confidence: 86%
“…Similar relations are observed for Bmal2 polymorphism rs7958822 in obese men and women (OR 2.2 and 2.7, resp.) [ 56 ] and the deletion/insertion of 54 base pair sequences of five repeat alleles on Per3 gene ( rs57875989 ) [ 57 , 58 ]. In contrast, the Per2 polymorphism rs7602358 is associated with a protection from type 2 diabetes in the UK population, which suggests that not all polymorphisms are negative for health [ 53 ].…”
Section: Clock Genes and Metabolic Disordermentioning
confidence: 99%
“…We have shown that a primate-specific, variable number, tandem repeat (VNTR), coding region polymorphism in human PER3 is associated with diurnal preference, delayed sleep phase disorder, sleep homeostasis, increased body mass index (BMI) in people who sleep late during work days, cognitive performance, fMRI-assessed brain activity, lower intelligence in people with long sleep duration during work days, and cardiac regulation (Archer et al, 2003;Viola et al, 2007Viola et al, , 2012Groeger et al, 2008;Vandewalle et al, 2009Vandewalle et al, , 2011Lazar et al, 2012;Lo et al, 2012). Others have reported associations with bipolar disorder (Benedetti et al, 2008), schizophrenia (Karthikeyan et al, 2014a), white matter integrity (Bollettini et al, 2017), type 2 diabetes (Karthikeyan et al, 2014b), cancer (Alexander et al, 2015), light sensitivity (Chellappa et al, 2012), hormone secretion (Wirth et al, 2013), cytokine secretion (Guess et al, 2009), and addiction (Zou et al, 2008). In addition, we have also shown that transgenically humanizing mouse Per3 with the VNTR polymorphism phenocopies some aspects of human sleep homeostasis such as increased theta power during wake and delta power during sleep (Hasan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%